Kemampuan Pemecahan Masalah Matematis Siswa Dengan Menggunakan Model Pembelajaran SSCS - Ika Meika; Ina Ramadina; Asep Sujana; Ratu Mauladaniyati (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2021)
Abstract This research is a descriptive study that aims to determine students’ problem solving abilites after using the SSCS learning model. The subjects of this study were 25 students of class VIII MTs Persis 72 Gunung Buntung. The learning process is carried out in accordance with the SSCS learning steps. The collection technique used tests and interviews. Based on the research result, it was foud that the percentage of students who had the ability to solve problem very well was 20%, the percentage of students who had good problem solving abilities was 72%, the percentage of students with sufficient problem-solving abilities 8%. Meanwhile, the highest percentage of problem solving ability indikator is identifying the coverage of data to solve the problem of 89,33%. Meanwhile, the lowest percentage of problem solving ability indicatoris checking the correctness of the results or answers by 64,32%. Keywords: Problem Solving Abilites, Learning Model, Search Solve Create Share, Abstrak Penelitian ini merupakan penelitian deskriptif bertujuan untuk mengetahui kemampuan pemecahan masalah siswa setelah menggunakan model pembelajaran SSCS. Subjek penelitian ini adalah siswa kelas VIII MTs Persis 72 Gunung Buntung berjumlah 25 orang. Proses pembelajaran yang dilaksanakan sesuai dengan langkah pembelajaran SSCS. Teknik pengumpulan yang digunakan tes dan wawancara. Berdasarkan hasil penelitian, diperoleh persentase siswa yang memiliki kemampuan pemecahkan masalah dengan sangat baik sebesar 20%, persentase siswa yang memiliki kemampuan pemecahan masalah dengan baik sebesar 72%, persentase siswa dengan kemampuan pemecahan masalah cukup sebesar 8%. Sedangkan persentase indikator kemampuan pemecahan masalah paling tinggi adalah mengidentifikasi kecakupan data untuk memecahkan masalah sebesar 89,33 %. Sedangkan Persentase indikator kemampuan pemecahan masalah paling rendah adalah Memeriksa kebenaran hasil atau jawaban sebesar 64,32%. Kata kunci: : Kemampuan Pemecahan Masalah, Model Pembelajaran, Search Solve Create Share